Divine revelation as source of knowledge - Jani, Mohd. Shah; Fatah Yasin, Raudlotul Firdaus (IIUM Press, International Islamic University Malaysia, 2019)
Islamisation of Knowledge (IOK) has been an important epistemological discourse within Muslim scholarship for the last three decades. This book is aimed to demonstrate that the texts of Divine Revelation, namely the Qur'an and sunnah of the prophet Muhammad (SAW), remain relevant as a source of knowledge and civilization in Islam. They were already well-integrated as theoretical foundations to found new discipline of knowledge and sciences in the past. This book believes that those texts of Divine Revelation will remain forever imperative to be an ontological critique to some theoritical frameworks of today's social and human sciences which are found to be predominantly secular, agnostic, materialistic, destructive and conflict-ridden. THis book does not claim to be a comprehensive reading of Islamisation discourse, but it certainly germane to both students of social-human sciences and students of Islamic Studies who are committed towards attempts at integrating Divine Revelation into, and making it relevant with, thier own disciplines of knowledge.